Pembuatan dan Pelatihan Tata Kelola Website Nagari Untuk Promosi Digital - Yuhefizar; Ikhsan Yusda Prima Putra; Yenida; Lilimiwirdi; Novadilastri; Witri Handayani; Variyetmi Wira; Hidra Amnur; Zulka Hendri; Deddy Prayama (Prosiding SISFOTEK, 2021)
The existence of a website in the current digitalization era has become a mandatory requirement for every Nagari (Village), as a promotional medium and an effort to digitize all business processes in the Nagari. For this reason, in this service activity an official village website was created and given website management training to village staff for digital promotion purposes. The website is equipped with menus that explain in detail the profile, potential, and facilities of the Nagari. Based on the results of a survey conducted after the training activities, it was concluded that an increase in the understanding of Nagari staff in managing the website was achieved by 90%, so that by utilizing the website media there was an increase in efficiency and effectiveness in digitally disseminating Nagari information to the wider community. This has a positive impact on the performance of the nagari government.